PENGEMBANGAN SKENARIO PEMBELAJARAN TEKS PROSEDUR BERBASIS PENDEKATAN SAINTIFIK PADA SISWA SMP KELAS VII - Elisabeth, Mery; Samhati, Siti; Mustofa, Ali (FKIP Universitas Lampung, 2020)
ABSTRACTThis study aims to develop a procedure text learning scenario based on a synthetic approach, test the feasibility and test the effectiveness of the Indonesian language learning scenario to achieve the learning objectives of identifying and concluding the procedure text.This study uses a research and development (R D) method proposed by Borg and Gall, in this study applying six steps starting from the preliminary study, planning, product design, product validation, field trials, and final products. The results of this study in the form of learning scenarios based on a scientific approach with the theme